The effects of acclimatization on blood clotting parameters in exertional heat stress - Vesic, Zoran; Vukasinovic-Vesic, Milica; Dincic, Dragan; Surbatovic, Maja; Radakovic, Sonja (Vojnosanitetski pregled, 2017)
Background/Aim. Exertional heat stress is a common problem in military services. Considering the coagulation abnormalities are of major importance in development of severe heat stroke, we wanted to examine changes in hemostatic parameters in soldiers during exertional heat stress test as well as the effects of a 10-day passive or active acclimatization in a climatic chamber. Methods. A total of 40 male soldiers with high aerobic capacity performed exertional heat stress test (EHST) either in cool [20ºC, 16ºC wet bulb globe temperature (WBGT)], or hot (40ºC, 29ºC, (WBGT) environment, unacclimatized (U) or after 10 days of passive (P) or active (A) acclimatization. Physiological strain was measured by tympanic temperatures (Tty) and heart rates (HR). Platelet count (PC), antithrombin III (AT), and prothrombin time (PT) were assessed in blood samples collected before and immediately after the EHST. Results. EHST in hot conditions induced physiological heat stress (increase in Tty and HR), with a significant increase in prothrombin time in the groups U and A. Platelet counts were significantly higher after the EHST compared to the basic levels in all the investigated groups, regardless environmental conditions and acclimatization state. Antithrombin levels were not affected by EHST whatsoever. Conclusion. In the trained soldiers, physiological heat stress caused mild changes in some serum parameters of blood clotting such as prothrombin time, while others such as antithrombin levels were not affected. Platelet counts were increased after EHST in all groups. A 10-day passive or active acclimatization in climatic chamber showed no effect on parameters investigated.   Key words: physical exertion; heat stress disorders; acclimatization; blood coagulation; military personnel; serbia.